Pseudomonas fluorescens group bacterial strains interact differently with pathogens during dual-species biofilm formation on stainless steel surfaces in milk - Zarei, Mehdi; Rahimi, Saeid; Saris, Per Erik Joakim; Yousefvand, Amin (Frontiers in Microbiology, 2022)
In order to develop strategies for preventing biofilm formation in the dairy industry, a deeper understanding of the interaction between different species during biofilm formation is necessary. Bacterial strains of the P. fluorescens group are known as the most important biofilm-formers on the surface of dairy processing equipment that may attract and/or shelter other spoilage or pathogenic bacteria. The present study used different strains of the P. fluorescens group as background microbiota of milk, and evaluated their interaction with Staphylococcus aureus, Bacillus cereus, Escherichia coli O157:H7, and Salmonella Typhimurium during dual-species biofilm formation on stainless steel surfaces. Two separate scenarios for dual-species biofilms were considered: concurrent inoculation of Pseudomonas and pathogen (CI), and delayed inoculation of pathogen to the pre-formed Pseudomonas biofilm (DI). The gram-positive pathogens used in this study did not form dual-species biofilms with P. fluorescens strains unless they were simultaneously inoculated with Pseudomonas strains. E. coli O157:H7 was able to form dual-species biofilms with all seven P. fluorescens group strains, both in concurrent (CI) and delayed (DI) inoculation. However, the percentage of contribution varied depending on the P. fluorescens strains and the inoculation scenario. S. Typhimurium contributed to biofilm formation with all seven P. fluorescens group strains under the CI scenario, with varying degrees of contribution. However, under the DI scenario, S. Typhimurium did not contribute to the biofilm formed by three of the seven P. fluorescens group strains. Overall, these are the first results to illustrate that the strains within the P. fluorescens group have significant differences in the formation of mono- or dual-species biofilms with pathogenic bacteria. Furthermore, the possibility of forming dual-species biofilms with pathogens depends on whether the pathogens form the biofilm simultaneously with the P. fluorescens group strains or whether these strains have already formed a biofilm.